Effectiveness of vasectomy using cautery - Barone, Mark A (BioMed Central, 2004)
BACKGROUND: Little evidence supports the use of any one vas occlusion method. Data from a number of studies now suggest that there are differences in effectiveness among different occlusion methods. The main objectives of this study were to estimate the effectiveness of vasectomy by cautery and to describe the trends in sperm counts after cautery vasectomy. Other objectives were to estimate time and number of ejaculations to success and to determine the predictive value of success at 12 weeks for final status at 24 weeks. METHODS: A prospective, non-comparative observational study was conducted between November 2001 and June 2002 at 4 centers in Brazil, Canada, the UK, and the US. Four hundred men who chose vasectomy were enrolled and followed for 6 months. Sites used their usual cautery vasectomy technique. Earlier and more frequent than normal semen analyses (2, 5, 8, 12, 16, 20, and 24 weeks after vasectomy) were performed. Planned outcomes included effectiveness (early failure based on semen analysis), trends in sperm counts, time and number of ejaculations to success, predictive value of success at 12 weeks for the outcome at 24 weeks, and safety evaluation. RESULTS: A total of 364 (91%) participants completed follow-up. The overall failure rate based on semen analysis was 0.8% (95% confidence interval 0.2, 2.3). By 12 weeks 96.4% of participants showed azoospermia or severe oligozoospermia (< 100,000 sperm/mL). The predictive value of a single severely oligozoospermia sample at 12 weeks for vasectomy success at the end of the study was 99.7%. One serious unrelated adverse event and no pregnancies were reported. CONCLUSION: Cautery is a very effective method for occluding the vas. Failure based on semen analysis is rare. In settings where semen analysis is not practical, using 12 weeks as a guideline for when men can rely on their vasectomy should lessen the risk of failure compared to using a guideline of 20 ejaculations after vasectomy.